Análise do nível de vulnerabilidade dos reservatórios de carbono em arbóreas funcionais de restinga e manguezal às variações do clima - Knupp, Karina Tiussi Batisti (2018)
Changes in climate have been taking place with implications for thermal regimes and precipitation. How plants will respond to these changes is still uncertain. In particular carbon pools, which account for up to 80% of the structural mass of plants. It is interesting to investigate the vulnerability level of some species of the coastal formations of restinga and mangrove of the Mata Atlântica biome of Greater Vitória - ES in relation to the variations of the climate. Therefore, the carbon storages contents in leaf and drain (stem) organs of Clusia hilariana, Ocotea notata and Protium icicariba restinga, and Avicennia schaueriana, Laguncularia racemosa and Rhizophora mangle were evaluated in the autumn of 2016 and summer of 2017. Data were related to temperature and precipitation values. Non-structural carbohydrates (starch, sucrose and total soluble carbohydrates) and cell wall structural polymers (cellulose, hemicellulose and lignin) were determined. Data were submitted to analysis of variance and Tukey test at the 5 % level (P <0.05) of significance, when necessary. The summer showed more precipitation. In the autumn of 2016 the average temperature was 27 ° C and in the summer of 2017, 25 ° C. The species of the two coastal formations responded differently to climate variations. In the mangrove, the concentration of cellulose in stem and leaf varied, being higher in the summer. In the restinga, the concentration of cellulose and starch in stem and leaf was higher in the summer. Similarly, in the restinga, the non-structural sucrose carbohydrate from the leaf, was also higher in summer. The concentration of lignin in the restinga was higher in the autumn. The restinga, due to changes in the concentrations of its carbon storages to temperature and precipitation variations between autumn and summer, can be considered, with greater vulnerability to temperature and precipitation changes in which ecosystems are being submitted.